Bayesian Compressive Sensing as Applied to Directions-of-Arrival Estimation in Planar Arrays. (14th July 2013) - Carlin, Matteo; Rocca, Paolo; Oliveri, Giacomo; Massa, Andrea
Abstract : The Bayesian compressive sensing (BCS) is applied to estimate the directions of arrival (DoAs) of narrow-band electromagnetic signals impinging on planar antenna arrangements. Starting from the measurement of the voltages induced at the output of the array elements, the performance of the BCS-based approach is evaluated when data are acquired at a single time instant and at consecutive time instants, respectively. Different signal configurations, planar array geometries, and noise conditions are taken into account, as well.